ANALISIS PEMBELAJARAN KURIKULUM MERDEKA DI SDN PLOSOKIDUL - Wyandha, Brillita; Purnama, Erninda Diknes; Primaridha, Monita Rizky; Damariswara, Rian (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Curriculum is a set of plans to achieve certain educational goals. Although the curriculum is often changed, the curriculum is an educational transformation through the Free Learning and Independent Campus policies to realize Indonesian Superior Human Resources with a Pancasila Student Profile. Students who have good cognitive abilities in written exams are not always able to apply their knowledge well in dealing with problems in everyday life. The purpose of the learning process is closely related to the evaluation of learning outcomes. The purpose of this article is to explain the self-learning curriculum assessment in elementary schools. In our opinion, the Merdeka Curriculum was designed by the government with the aim of perfecting the previous curriculum. These changes are taking place in accordance with the times and changes are starting to appear, the contents of the Merdeka Curriculum are almost similar to the 2006 KTSP curriculum, but in this Independent Curriculum it emphasizes the publication of project learning outcomes. Keywords: Independent Curriculum, Teachers, Students, Education